Axillary Artery Pseudoaneurysm After Revision Plate Osteosynthesis of a Midshaft Clavicle Fracture Nonunion: A Case Report. Issue 3 (23rd July 2020) - Firoozabadi, Reza; Wilkerson, Jacob; Hemingway, Jake; Tran, Nam
Abstract : Case: A patient with history of nonunion repair of traumatic midshaft clavicle fracture was referred to our orthopaedic trauma clinic for new-onset shoulder pain and paresthesias involving the ipsilateral arm. Computed tomography angiography revealed an axillary artery pseudoaneurysm adjacent to the instrumentation and recurrent nonunion of the fracture site. The patient underwent coil embolization of the pseudoaneurysm and nonunion repair. Conclusion: This case demonstrates that iatrogenic neurovascular injury during clavicle fracture nonunion repairs can present in a delayed fashion requiring more thorough clinical and imaging evaluation to achieve successful treatment.